Translational medicine and drug discovery - Littman, Bruce H., 1944-; Krishna, Rajesh (New York : Cambridge University Press, 2011)
'Focuses on the new discipline of translational medicine as it pertains to drug development within the pharmaceutical and biotechnology industry'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Drug Discovery; Translational Medical Research -- methods